Advances in industrial and labor relations, 2017. Vol. 24, - Lewin, David, active 2018; Gollan, Paul (Advances in industrial and labor relations ;, 2018)
Volume 24 of Advances in Industrial and Labor Relations (AILR) contains eight papers highlighting important aspects of the employment relationship. The papers deal with such themes as shifts in workplace voice, justice, negotiation and conflict resolution in contemporary workplaces. Consistent with previous AILR volumes, the papers in Volume 24 reflect a variety of quantitative and qualitative research methods, including case studies, survey, interviews, historiography, theory building, and longitudinal and cross-sectional research designs and analysis. These papers also reflect a global perspective on workplace issues. The specific topics of these papers include social construction of workarounds, workplace dispute resolution, employee involvement at Delta Air Lines, voice and empowerment practice in an Australian manufacturing company, democracy and union militancy and revitalization, adapting union administrative practices to new realities, pro-social and self-interest motivations for unionism and implications for unions as institutions, and high performance work systems and union impacts on employee turnover intention in China.